URBAN HOUSING DEVELOPMENT: TOWN PLANNING ISSUES - Mohd @ Ahmad, Ibrahim; Arbin, Ezrin; Ramly, Ahmad (PLANNING MALAYSIA, 2007)
Town planning is seen to have imposed some degree of constraint on housing development and is discussed in a voluminous literature on the relationship between the planning system and housing land supply. The constraints are believed to have partly contributed to the increase in housing production costs leading to a mismatch between housing supply and demand. Since the government has entrusted the private sector to play an important and bigger role to meet housing needs, local planning authorities and planners should be more cautious in fulfilling their role in housing development. This paper attempts to raise some pivotal aspects of town planning that relate to the problems associated with housing land development in West Malaysia. The primary data was gathered through personal interviews with selected housing developers and analyzed using the factor analysis tool in SPSS. The result of the analysis shows that several aspects of town planning are strongly correlated with development plans and development control factors particularly on land identified for housing, layout plan approval and complying with planning standards.